Empathy in Psychosocial Intervention: a theoretical overview - Stanley, Selwyn (International Journal of Psychosocial Rehabilitation, 2016)
Empathy is a concept that is found in the lexicon of many of the ‘helping professions’ be it medicine, nursing, education or social work to name a few. It is a key element that determines professional competence and considered necessary for effective relationship based practice. Almost all training programs within the helping professions strive to incorporate this ability within the skills repertoire of budding professionals. Empathy is not a new concept in practice and reference to it can be traced to the writings of early case workers. It has been considered to be vital in building trust and developing a relationship that will foster growth and change (Pinderhughes, 1979). Carl Roger’s person centred approach envisages empathy to be one of the core conditions of the positive, purposeful and professional relationship that practitioners strive to establish with clients. Empathy enables one to see external events through the client’s eye lens and thus provides a near accurate subjective perception of distressful environmental stressors and the realities of the client’s life situation. This is important to understand how oppression is experienced by the ‘other’ if one wants to help alleviate distress. Key tasks of capacity building, resource mobilisation and conscientization would only be possible if the practitioner has a near-accurate perception of the client’s life scenario. While empathy is certainly a virtue in helping, there are also dangers associated with boundary cross over, an issue that practitioners need to be cautious about. This paper looks at the nature, structure and types of empathy and examines its importance in psychosocial intervention. It explores its links with establishing rapport with clients, to resilience, social justice and empowerment; concepts which are of central concern to a psychosocial approach. Finally it discusses barriers in the manifestation of empathy and its relationship to compassion fatigue and burnout.